Pengaruh Komitmen Agama Dan Atribut Produk Islam Terhadap Kepercayaan Nasabah Menggunakan Jasa Lembaga Keuangan Syariah - Sri Riska Ananda Lubis; Annio Indah Lestari; Nikmah Dalimunthe (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
This research aims to find out and analyze how much influence religious commitment and Islamic product attributes have on customer trust in using the services of a case study sharia financial institution at Bank Sumut, Lubuk Pakam Syariah Sub Branch. This research uses a quantitative type of research with one dependent variable, namely customer trust and two independent variables, namely religious commitment and Islamic product attributes. This research uses primary data, using data collection methods through questionnaires. The data analysis techniques used in this research are descriptive tests, validity tests, reliability tests, classical assumption tests (normality test, multicollinearity test, heteroscedasticity test) and hypothesis tests (coefficient of determination test (R2), partial significance test (t-test) , simultaneous significance test (f-test) and multiple linear regression test)). The results of this research reveal that religious commitment has a positive and significant effect on customer confidence in using the services of sharia financial institutions based on test results which show that the coefficient table shows that the tcount value is greater than ttable, namely 19,245 > 1,666 with a probability value of 0.915 or smaller than 5 % (0.05). And Islamic product attributes have a positive and significant effect on customer trust based on test results which show that the coefficient table shows that the tcount value is greater than ttable, namely 6,125 > 1,666 with a probability value of 0.108, meaning it is smaller than 5% (0.05). Islamic product attributes and customer trust simultaneously have a positive and significant effect on customer trust. From the results of the F test with df(n1)=k-1=2 and df(n2)=n-k=32, it is obtained that Fcount is greater than the ttable value, namely 189.181 3.12 with a significance level of 0.000, it means it is smaller than 5% (0.05).